Transformation of the economic policy of the state in terms of globalization tendencies of modern development - Свиридюк, Наталія Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This paper argues the case for the transformation of economic policy in terms of cooperation with supranational organizations and the general globalization trends of world development. The content and the specific implementation of economic policy in terms of European and international integration. The influence of the globalization of the world economy on the development and implementation of domestic economic functions of the state. The main problems facing Ukraine as a country with an unstable economic system associated with its current state of legal and socio-economic development.